2014
DOI: 10.1038/nrg3853
|View full text |Cite
|
Sign up to set email alerts
|

Competition between target sites of regulators shapes post-transcriptional gene regulation

Abstract: Post-transcriptional gene regulation (PTGR) of mRNA turnover, localization and translation is mediated by microRNAs (miRNAs) and RNA-binding proteins (RBPs). These regulators exert their effects by binding to specific sequences within their target mRNAs. Increasing evidence suggests that competition for binding is a fundamental principle of PTGR. Not only can miRNAs be sequestered and neutralized by the targets with which they interact through a process termed 'sponging', but competition between binding sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
238
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(246 citation statements)
references
References 128 publications
5
238
0
Order By: Relevance
“…Our work suggested that the widespread MREs could act as a pool of sponges to sequester shared miRNAs and enhance the threshold behavior of miRNA repression for targets that have expression levels around the threshold, thus increasing the sensitivity of miRNA regulation on these primary targets. During the revision of this paper, a theoretical study further supported this hypothesis (27).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Our work suggested that the widespread MREs could act as a pool of sponges to sequester shared miRNAs and enhance the threshold behavior of miRNA repression for targets that have expression levels around the threshold, thus increasing the sensitivity of miRNA regulation on these primary targets. During the revision of this paper, a theoretical study further supported this hypothesis (27).…”
Section: Discussionmentioning
confidence: 58%
“…According to this hypothesis, although the ceRNA regulation could be widespread (3), in most cases, such a regulation generates only a weak derepression effect (21). Dramatic ceRNA-mediated derepression may be mainly restricted to highly expressed long noncoding RNAs, circular RNAs, or transcripts in specific physiological or disease conditions (27).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the highly expressed, liver-specific miR-122 has been shown in vitro and in vivo to be insensitive to ceRNA-based regulation. The derepression of its targets can in fact occur only if a competitive RNA is exogenously administered at a concentration that is vastly exceeding that of any endogenous transcript [56,57].…”
Section: (Pten)-cernas: Open Questionsmentioning
confidence: 99%
“…Whether circRNA abundance or target site numbers within the circRNA comply with an expected effect on miRNA activity awaits clarification. This is also a controversial matter for competing endogenous RNA (ceRNAs) [37], which also bind miRNAs and function to titrate miRNAs away from the intended targets. Although both the linear ceRNAs and circRNAs regulate miRNA function, the efficiency with which this is carried out may differ.…”
Section: Circrnas As Sponge or Decoysmentioning
confidence: 99%